Kompetensi Mahasiswa Pendidikan Profesi Guru (PPG) dalam Mengembangkan Perangkat Pembelajaran Berbasis Problem-Based Learning dan Project-Based Learning - Amelia Widya Hanindita; Agung Pramujiono (Universitas Muhammadiyah Jember, 2026)
Teacher pedagogical competence, particularly in developing learning tools, is a key factor in the successful implementation of innovative learning in the classroom. The Teacher Professional Education Program (PPG) is designed to strengthen these competencies, including students' ability to design Problem-Based Learning (PBL) and Project-Based Learning (PjBL)-based learning tools relevant to the demands of the Independent Curriculum and 21st-century learning. This study aims to describe the competencies of In-Service PPG students in developing PBL and PjBL-based learning tools. The study used a descriptive qualitative approach with 12 In-Service PPG Batch III students in 2023, Universitas PGRI Adi Buana Surabaya, as subjects. Data were obtained through documentation of learning tools including lesson plans (RPP), teaching materials, student worksheets (LKPD), learning media, and assessment instruments and rubrics. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that, in general, the PPG students' ability in developing PBL and PjBL-based learning tools was in the very good category, with an average overall score of 92.7. However, PPG students demonstrated more mature competencies in developing PBL-based tools compared to PjBL, particularly in terms of tool completeness and appropriateness of learning syntax implementation. This finding indicates the need for more intensive mentoring and training related to the development of PjBL-based learning tools, particularly in project planning and authentic assessment, so that PPG students' pedagogical competencies develop in a more balanced and optimal manner.